The Influence of the Probalusan Learning Model on the Attitudes and Science Learning Outcomes of Grade VIII Students at SMP Negeri 6 Sentani, Jayapura Regency - Rosaniya E. Rehiara; Leonardo Elisa Aisoi; Agustinus Tandilo Mamma (Jurnal Penelitian Pendidikan IPA, 2025)
Science is a fundamental discipline that aims not only to transfer factual knowledge but also to develop critical, logical, and analytical thinking skills in students. This study aims to analyze the effect of the Probalusan learning model (Problem-Based Learning and Susan Loucks Horsley based on problem solving, discussion, and collaboration) on the attitudes and learning outcomes of eighth-grade students of SMP Negeri 6 Sentani. The Probalusan model was chosen because it has the potential to increase active student participation, foster curiosity, and facilitate the understanding of science concepts through solving real problems. This study uses a quantitative approach with a quasi-experimental design, namely a pretest-posttest control group design. The study population was all eighth-grade students, with two classes selected as samples: one experimental class using the Probalusan model, and one control class using conventional methods. The instruments used included a learning attitude questionnaire and a science learning outcome test. Data analysis was carried out using statistical tests, namely normality, homogeneity, t-test, and N-Gain tests. The results of the t-test on the posttest data showed a significant difference between the control class and the experimental class. The results showed that science learning using the Probalusan model can improve students' attitudes and learning outcomes.